ALOKASI SUMBERDAYA KAWASAN HUTAN RAKYAT KABUPATEN SUKABUMI, JAWA BARAT: PENDEKATAN MULTI-OBJECTIVE PROGRAMMING - Fahmi, Innike Abdillah; Winandi, Ratna; Kusnadi, Nunung (Jurnal Agribisnis Indonesia, 2013)
The economic and ecological objectives in the development of private forest are conflicting, thus led to deforestation. The objectives of the study were to analyzeÂ factors affecting farmersâs decision in determining for the aim (economic or ecological objectives) of their land management by using logistic regession, andÂ to analyze resources allocation in private forest that gives the best compromise solution between economic and ecological objectives by multi-objective programming approach and scenarios. The result shows that farmers are still economic oriented in determining the aim of their land management, mostly affected by number of farm household, off-farm income, participation in farmer group meeting, participation in extention meeting and farmerâs experiance in farm factors. Land management scenario that the closest to the target value (Rp 39.907 billion per year) is land management with minimum land area requirement, so that the value received by farmers is Rp 21.038 billion per year. Capital is a limitting factor in optimizing the use of available resources.